2008
DOI: 10.1007/s12253-008-9107-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Angiogenic Factors and their Prognostic Relevance in Bladder Cancer

Abstract: Angiogenesis plays a critical role in tumor growth. VEGF, angiopoietins (Ang-1, Ang-2) and their tyrosine kinase receptor Tie2 are major regulators of angiogenesis. The aim of this study was to evaluate the prognostic value of the serum levels of these factors in bladder cancer. We analyzed the serum samples of 117 bladder cancer patients and 64 healthy volunteers by enzyme linked immunosorbent assay (ELISA) for Ang-1, Ang-2, VEGF and the extracellular domain of Tie2. The statistical evaluation of the obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 28 publications
2
24
0
3
Order By: Relevance
“…However, conflicting results were showed in other studies regarding the ability of VEGF to predict prognosis in bladder cancer (Suzuki et al, 2005;Nadaoka et al, 2008;Szarvas et al, 2008;Szarvas et al, 2009;Ma et al, 2010;Zaravinos et al, 2012).…”
mentioning
confidence: 93%
“…However, conflicting results were showed in other studies regarding the ability of VEGF to predict prognosis in bladder cancer (Suzuki et al, 2005;Nadaoka et al, 2008;Szarvas et al, 2008;Szarvas et al, 2009;Ma et al, 2010;Zaravinos et al, 2012).…”
mentioning
confidence: 93%
“…Other studies on Ang-1 and Ang-2 demonstrated the presence of significantly higher serum levels of Ang-1 in patients with bladder cancer relative to the control; and conversely, Ang-2 and Tie2 levels were significantly lower. (Szarvas, et al, 2009). The same study also showed that high Tie2 serum level was an independent prognostic factor for metastasis in multivariate analysis model that included tumor grade and stage.…”
Section: Ang Family In Cancers Including Bladder Cancermentioning
confidence: 76%
“…Tumor invasion and progression in the bladder represent a multifactorial process affected by imbalance between angiogenic and antiangiogenic factors (9). VEGF and MMP are two of the most important angiogenic factors, while TSP-1 and (10) reported that muscular invasiveness of bladder carcinoma was significantly correlated with serum VEGF level, suggesting that VEGF stimulated proliferation and invasion of tumor via VEGF-2.…”
Section: Discussionmentioning
confidence: 99%